Constants and variables of GOA or the high school for visually impaired at the beginning of the 21 century - Antov, Ivan (Journal of Exceptional People, 2012)
The paper refl ects main changes which happened in the high school for visually impaired in the last decade. It is focused on substitution of the exclusive postition of the special school for a possibility of a choice of the pupil (and the family) where to be educated., on providing mainstream high schools integrating visually impaired pupils with methodological support, on strengthening competitiveness of the school, on interdisciplinary cooperation etc. Simultaneously, it emphasizes positive values accompanying the school in the period of its existence. In addition to educational activities obliging the students with special needs, the school provides a wide scale of activities to prepare students with visual impairment for independent life. Analysis of constants and variables in the development of the school as well as insertion into the context of contemporary conditions enables to indicate prospects of the school.
Keywords: Education of Persons with Visual Disabilities; Speech Recognition Software; Adolescent; pomůcky pro komunikaci postižených; Communication Devices for People with Disabilities; integrovaná výuka; lidé; výuka zrakově postižených; Persons with Visual Disabilities; zrakově postižení; software pro rozpoznávání řeči; Mainstreaming, Education; mladiství; Humans